Efektivitas Beberapa Jenis Pupuk Hayati Terhadap Produksi Kacang Merah Varietas Inerie - Lewar, Yosefina; Hasan, Ali; Vertygo, Stormy (Politeknik Negeri Lampung., 2023)
The purpose of this study was to examine the best types biofertilizers in increasing the growth and yield of kidney bean of the Inerie variety in the lowlands. The research was conducted in July - November 2022 located on farmer's land. The study used a randomized block design with the factors studied were the types biofertilizer, namely: H0 : Without biological fertilizers, H1 : Liquid Organic Biofertilizer, H2 : Bion-Up, H3 : M-Bio, H4 : Bio-Conversion, H5 : Bio HYT , H6 : Bioboost, and H7 : Bio CBA Grow. The results showed that the bioboost biofertilizer was more effective on the growth and yield of the kidney bean variety Inerie variety in the lowlands, namely the net assimilation rate of 0.00559 g/cm2/week, total leaf chlorophyll 17.632 mg/g, number of pods containing 14.344 pods, total seeds 43.281 grains, and seed weight 14.713 g. Keywords: kidney bean, biofertilizer, Inerie variety